Small-scale robots inspired by aquatic interfacial biolocomotion - Kim, Dongjin; Park, Chan Jin; Koh, Je Sung; Ha, Jonghyun (MRS Bulletin, 2024)
Bioinspired semiaquatic robots have a remarkable ability to effectively navigate on the water surface. In this article, we explore the design of these biomimetic robotic systems and their body scale-dependent governing forces behind the motion. First, the role of surface tension in enabling hydrophobic objects to remain afloat despite having greater density than water and the effect of morphology, especially the presence of hair-like structures, on the flotation stability are discussed. Then the forces that drive the diverse motions of natural organisms and robots on the air/water interface are investigated. We highlight that while small organisms and robots generate motion utilizing surface tension-based force, large ones primarily exploit inertial drag for propulsion. We show the correlation between the performance and body size in both small and large natural organisms, and how they adjust the shape and speed of legs to optimize the propulsion. To optimize these distinct propulsion forces, the shape and speed of the driving legs are adjusted, thereby maximizing momentum while maintaining high efficiency. This article aims to provide insights on the design and operating mechanism of semiaquatic robots and to bridge the gap between the study of biological locomotion and its mechanical analogs. Graphical Abstract: (Figure presented.)
Keywords: Air/Water Interfaces; Biolocomotion; Biomimetic robotics; Hydrophobics; Interfacial locomotion; Performance; Robotic systems; Semiaquatic robot; Small scale; Water surface; Biomechanics; Biomimetics; Interfacial locomotion; Semiaquatic robots